PRODUCTION OF ENZYMATIC COMPLEX IN SOLID STATE FERMENTATION BY Trichoderma sp. USING PALMOIL EMPTY FRUIT PALM OIL BUNCH (EFB) AS SUBSTRATE - RODRÍGUEZ G., Ibeth; PIÑEROS C., Yineth (Vitae, 2009)
The oil palm industry in Colombia, the fifth world manufacter, generates lignocelulosic waste like the empty fruit bunch (EFB), which remains after removing the fruit of oil palm. Keeping in mind this characteristic, it can be used as substrate for cellulases production. In this study we evaluate the productivity of cellulases through native crop of Trichoderma viride T12 using EFB. The wastes are subject to chemical (HNO3 0,5% y 1%) and biological treatments (previous cultivate with Pleurotus ostreatus during 10 and 20 days), to get its deslignification and improving the production of cellulases. The evaluation of the activities of total cellulase (FPase) and endoglucanase (CMCase) was made after 8 days of cultivate by fermentation in solid state, using pretreated wastes as substrate. It was supplemented with two inorganic nitrogen sources (NH4H2PO4 y NaNO3). The major celulolitic activities were found in wastes treated with precultive of Pleurotus ostreatus and NaNO3 as nitrogen source, with values of 0,374 U/mL of FPase and 0,776 U/mL of CMCase. All activities were expressed in micromole of glucose units (U) of substrate hydrolyzed in 1 min.